Second Five Year Plan Assam a Review of Progress - Planning Commission (Planning Commission, 1958)
For the Second Plan of Assam, the Planning Commission had approved a total outlay of Rs. 57.94 crores. Against this allocation a total expenditure of about Rs. 54.50 crores was incurred. This is against the First Plan expenditure of Rs. 20.50 crores. During 1958-59, in view of foreign exchange difficulties, the Planning Commission reduced the outlay on the National Plan from Rs. 4,800 crores to Rs. 4,500 crores. Ultimately, However the expenditure on the National Second Plan was about Rs. 4,600 crores, judged by the expenditure against the original outlay, plan performance in the State, during the Second Plan, was quite in keeping with the revised outlay under the National Plan.
Planning and Development Department, Government of Assam